(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
A hundred years old man was admitted in NIO&H with the diagnosis of cataract in right eye.He was scheduled for operation under local anaesthesia, but on the O.T. table he became restless, non cooperative. So, the surgical team planned to do the operation under general anaesthesia. Necessary investigations for GA done and the patient was found nondiabetic but had anterolateral ischaemia and had cardiomegaly in X-ray chest. Our anaesthetic plan was to do the surgery under sedation with local anaesthetic block (MAC). We provided the patient monitored anaesthesia care (MAC) by giving Inj. Fentanyl, Inj.Midazolam and Inj. Propofol. The operation took twenty five minutes. Initially after the administration of drugs,his SPO2 fell down.Oxygen given and SPO2 increased to 99% within 90 seconds. Throughout the peroperative period patient remained haemodynamically stable. Within 10 minutes,he opened his eyes,responded to vocal command and after one hour, he was shifted from postoperative ward to general ward. Journal of Bangladesh Society of Anaesthesiologists 2014; 27(1): 36-38